Pengaruh Ukuran Kantor Akuntan Publik, Profitabilitas, Dan Leverage Terhadap Pergantian Auditor - Muhammad Fauzan Ramadhan; Fachriyah, Nurul (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
Abstract: This study aims to determine the effect of the size of a public accounting firm, company profitability, and the level of leverage in a company on auditor switching which is proxied by a dummy variable. The object of this study is a state-owned company listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. Determination of the sample was determined by using purposive sampling method in order to obtain 60 research samples. This study uses an analytical method, namely logistic regression analysis with the help of the IBM SPSS 25 application. The results show that public accountant firm size has a positive effect on auditor switching, profitability has a positive effect on auditor switching, and leverage has a negative effect on auditor switching.